Mass production of polyacrylonitrile sub-micron fibrous webs with different aligned degrees via free surface electrospinning for air purification. Issue 15 (August 2022) - Zhou, Mengjuan; Fan, Qi; Quan, Zhenzhen; Zhang, Hongnan; Wang, Liming; Qin, Xiaohong; Wang, Rongwu; Yu, Jianyong
Atmospheric pollution has emerged as causing irreversible harm to the ecosystem and people. Sub-micron fibrous filters play an incomparable role in effective air purification, owing to their excellent internal connectivity. Herein, three-dimensional sub-micron fibrous webs with various aligned degrees were conveniently fabricated via free surface electrospinning with different rotation speeds of the roller with a large diameter in large quantity, applied in air filtration. The influence of the orientation degrees of fibers on the performances of the fibrous filter was analyzed systematically. Results showed that the filtration performance of fibrous filters was inversely proportional to the orientation degree of the sub-micron fibers. Random fibrous webs with areal densities of ≤2.0 g m −2 exhibited high porosity (∼90%), ensuring qualified air permeability and outstanding filtration efficiency from 92% to 99.5% for ultra-fine aerosol particles (∼0.26 µm) under a higher air velocity of 14.1 cm s −1 . The internal aperture channels were twists and turns with irregular polygon shape for random fibrous webs, while they were a narrow strip in the horizontal and straight in the longitudinal for aligned ones, which influenced the filter's performances. Fibrous webs with better orientation of fibers and larger pore size are beneficial for energy efficiency and exhibited good filtration performance, better air permeability, and an improved mechanical property along the longitudinal direction. A cost-effective uniform sub-micron fibrous filter with different aligned degrees could be produced rapidly via free surface electrospinning with a mass production rate, which is beneficial for industrial production and commercial applications in respiratory protection and indoor air purification for precise purification of air pollution.